The contradictory influence of velocity: representational momentum in the tactile modality - Merz, S; Deller, J; Meyerhoff, H; Spence, C; Frings, C (American Physiological Society, 2019)
Representational momentum (RM) is the term used to describe a systematic mislocalization of dynamic stimuli, a forward shift; that is, an overestimation of the location of a stimulus along its anticipated trajectory. In the present study, we investigate the effect of velocity on tactile RM, because two distinct and contrasting predictions can be made, based on different theoretical accounts. According to classical accounts of RM, based on numerous visual and auditory RM studies, an increase of the forward shift with increasing target velocity is predicted. In contrast, theoretical accounts explaining spatiotemporal tactile illusions such as the tau or cutaneous rabbit effect predict a decrease of the forward shift with increasing target velocity. In three experiments reported here, a tactile experimental setup modeled on existing RM setups was implemented. Participants indicated the last location of a sequence of three tactile stimuli, which either did or did not imply motion in a consistent direction toward the elbow/wrist. Velocity was manipulated by changing the interstimulus interval as well as the duration of the stimuli. The results reveal that increasing target velocity led to a decrease and even a reversal of the forward shift, resulting in a backward shift. This result is consistent with predictions based on the evidence from tactile spatiotemporal illusions. The theoretical implications of these results for RM are discussed.